Indirect Digital Radiography versus Conventional Radiography for Estimation of Root Canal Length (Mustansiria Dental Journal, 2018)
The aim of this study was to evaluate the accuracy of Indirect Digital Radiography (IDR) for setting working length with the aid of new software additions program. The root canal length was measured using two estimation methods: conventional D-speed film radiograph, IDR using 2 clicks, 3 clicks, 4 clicks, and 6 clicks of measuring tools. Twenty seven extracted human lower molar teeth with different canal curvatures were examined. True canal length was measured using a millimeter rule. Non-significant differences were found in canal length estimation between IDR, conventional radiograph, and true canal length, also there was non-significant difference in measurement using 2, 3, 4, or 6 clicks.